LIBERTY AS THE IMPOSSIBLE, THE LANGUAGE OF SILENCE: IN REREADING KIM SUYǑNG’S WORKS IN 1960s - CHOI, Seoyoon (International Journal of Korean Humanities and Social Sciences, 2017)
This article examines several works written by Kim Suyǒng in the 1960s with a focus on negation as the poetic method in accordance with revolution. He lived through a late colonial period, the Korean War, the April Revolution, and Park Chung Hee’s regime and he was keenly aware Koreans had not spoken of liberty as the invention of modernity in our mother tongue throughout our history. He dedicated all his poems to demonstrating why liberty was impossible to be spoken in Korean. In the course of his writing, his authentic poetic language developed into silence as a martyr, the language of death and love. In so doing, he could “live liberty” through his poetry in accordance with his conscience in the authoritarian society.